Grounding digital mental health and wellbeing platform development in a theory of change: a convergent mixed methods approach - Cowling, Emily P.; Misch, Regina; Sugarman, Georgia; Sammut, Samaryah; Hanley, Terry; Sugarman, Roy; Green, Lynne; Johnston, Patrick; Ramos, Tamara; Rock, Brian; Wilson, Hannah; Salhi, Louisa (Frontiers in Psychiatry, 2025)
BackgroundMental health concerns among children and young people are rising, yet only a fraction receive the care they need. Digital mental health solutions can help bridge this gap, and recent years have seen a rapid proliferation of mental health applications. However, many lack a clear framework detailing how their activities lead to meaningful outcomes. A theory of change articulates these pathways, informing the development, implementation and evaluation of such technologies. Using a case illustration, this paper presents the practical application of developing a theory of change for a digital mental health intervention.MethodsIn 2024, Kooth Digital Health launched a digital mental health platform, Soluna, to all 13-to-25 year olds in California. Its development was grounded in a theory of change, co-created with youth, service staff, and external experts. A convergent mixed methods design was utilized to develop the theory of change across three phases of work via a digital diary, workshop series and express media survey. Using an iterative approach, data analyzed from one phase influenced the next. Qualitative data were analyzed using rapid deductive analysis and quantitative data were summarized using descriptive statistics.ResultsIn the insight generation phase, 50 youth completed a digital diary while using the proof-of-concept application. Findings suggested youth sought autonomy, relatedness, and self-efficacy, central to their engagement and desired outcomes. The framework development phase engaged 18 service staff and two external experts via workshops to define the theory of change, mapping the platform’s features to intended outcomes. In the dissemination design phase, 12 youth provided survey feedback on the theory of change, validating that its key concepts resonated with them and informing content clarity revisions.ConclusionsThe methodology led to recommendations for developing a theory of change for industry applications: (i) consult diverse stakeholders, including youth, throughout, (ii) utilize a mixed methods design to triangulate data, (iii) leverage interactive methods to facilitate data collection, (iv) be flexible in the approach, and (v) engage advocates. Applying these methods can help developers and researchers design, implement and evaluate digital mental health interventions that are user-centered and effective.